2006
DOI: 10.1055/s-2006-925340
|View full text |Cite
|
Sign up to set email alerts
|

The Yield of Capsule Endoscopy in Patients with Abdominal Pain or Diarrhea

Abstract: Capsule endoscopy had a low yield for evaluation of abdominal pain or diarrhea and cannot be recommended as a first-line test without further study. Nonetheless, it facilitated diagnosis in 9 % of patients with negative endoscopic and radiologic examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 19 publications
3
40
0
5
Order By: Relevance
“…Suspicion of Crohn’s disease was previously left to the discretion of the treating physician and usually was considered when a patient had either abdominal pain or persistent diarrhea. Yields of capsule endoscopy are low when performed in patients with abdominal pain alone and in patients with abdominal pain and diarrhea alone [6,7]. When other criteria are added this yield increases.…”
Section: Suspected Crohn’s Diseasementioning
confidence: 99%
“…Suspicion of Crohn’s disease was previously left to the discretion of the treating physician and usually was considered when a patient had either abdominal pain or persistent diarrhea. Yields of capsule endoscopy are low when performed in patients with abdominal pain alone and in patients with abdominal pain and diarrhea alone [6,7]. When other criteria are added this yield increases.…”
Section: Suspected Crohn’s Diseasementioning
confidence: 99%
“…In a prospective blinded study, VCE had superior diagnostic accuracy when compared to MRE and CTE in Crohn's disease [77]. In patients with abdominal pain and/or diarrhea, without associated findings of weight loss/growth failure, elevated inflammatory makers or abnormal imaging studies, the yield of capsule endoscopy is low [78,79]. Because VCE has a high risk of capsule retention in Crohn's disease, CTE or MRE is useful to detect small bowel wall thickening or stricture before considering VCE (Fig.…”
Section: Ulcerating Diseasementioning
confidence: 97%
“…Occult GI bleeding accounts for up to two-thirds of SBCE studies performed [12]. It was shown that 20-38 % of patients with normal upper and lower endoscopy have significant intestinal lesions [13,14] (Fig.…”
Section: Occult Gi Bleedingmentioning
confidence: 99%